Application of High-Frequency Conductivity Map Using MRI to Evaluate It in the Brain of Alzheimer's Disease Patients - Park, Soonchan; Jung, Sue Min; Lee, Mun Bae; Rhee, Hak Young; Ryu, Chang-Woo; Cho, Ah Rang; Kwon, Oh In; Jahng, Geon-Ho (Frontiers in Neurology, 2022)
Background: Previous studies reported increased concentrations of metallic ions, imbalanced Na+ and K+ ions, and the increased mobility of protons by microstructural disruptions in Alzheimer’s disease (AD). Purpose: 1) to apply a high-frequency conductivity (HFC) mapping technique using a clinical 3T MRI system, 2) compare HFC values in the brains of participants with AD, amnestic mild cognitive impairment (MCI), and cognitively normal (CN) elderly people, 3) evaluate the relationship between HFC values and cognitive decline, and 4) explore usefulness of HFC values as an imaging biomarker to evaluate the differentiation of AD from CN. Materials and Methods: This prospective study included 74 participants (23 AD patients, 27 amnestic MCI patients, and 24 CN elderly people) to explore the clinical application of HFC mapping in the brain from March 2019 to August 2021. We performed statistical analyses to compare HFC maps between the three participant groups, evaluate the association of HFC maps with Mini-Mental State Examination (MMSE) scores, and to evaluate the differentiation between the participant groups for HFC values for some brain areas. Results: We obtained a good HFC map noninvasively. The HFC value was higher in the AD group than in the CN and MCI groups. MMSE scores were negatively associated with HFC values. Age was positively associated with HFC values. The HFC value in the insula has a high area under the ROC curve (AUC) value to differentiate AD patients from the CN participants (Sensitivity (SE) = 82, Specificity (SP) =97, AUC = 0.902, p < 0.0001), better than GMV in hippocampus (SE = 79, SP =83, AUC = 0.880, p < 0.0001). The classification for differentiating AD from CN was highest by adding the hippocampal GMV to the insular HFC value (SE = 87, SP = 87, AUC = 0.928, p < 0.0001). Conclusion: HFC values were significantly increased in the AD group compared to the CN group and increased with age and disease severity. HFC values of the insula along with the GMV of the hippocampus can be used as an imaging biomarker to improve the differentiation of AD from CN.